Innovative gene targeted treatments for osteosarcoma: a mini review of current clinical evidence and future prospects - Hu, Dong; Yu, Xingxing; Xu, Junkui; Li, Bingbing; Ou, Xuehai; Shi, Shaoyan (Frontiers in Medicine, 2025)
Osteosarcoma is the most common primary malignant bone tumor in adolescents and young adults, marked by genomic instability and a high rate of lung metastasis. While surgery and intensive chemotherapy have improved survival for localized disease, outcomes for recurrent or metastatic cases remain poor, with limited progress in recent decades. In response, targeted therapies have emerged, focusing on key oncogenic pathways and tumor microenvironmental factors. Recent clinical studies have explored tyrosine kinase inhibitors (e.g., sorafenib, regorafenib), PI3K/Akt/mTOR inhibitors, angiogenesis modulators (e.g., apatinib), and immune checkpoint inhibitors. Although some agents achieve transient disease stabilization or partial responses, their overall efficacy is constrained by tumor heterogeneity, rapid resistance, and the lack of predictive biomarkers. Notably, combination regimens—such as VEGF and mTOR inhibition or TKI with immunotherapy—have shown promise in preclinical and early clinical trials. Future directions emphasize precision medicine approaches, including liquid biopsies and molecular profiling to guide therapy selection. Nanotechnology-based delivery systems are also under development to enhance tumor targeting and reduce systemic toxicity. However, the rarity of osteosarcoma, trial design limitations, and treatment-related toxicities remain critical barriers. This review synthesizes current evidence and underscores the need for biomarker-driven, multimodal strategies to overcome resistance and improve long-term outcomes in osteosarcoma management.